Improved drinking water, healthier children? Evidence from Pakistan - Javed, Rashid; Mughal, Mazhar (International journal of social economics, 2025)
Purpose One of the United Nations’ sustainable development goals is to ensure the availability of improved drinking water for everyone. In this study, we examine the association between access to improved drinking water at the district level and child nutritional outcomes in Pakistan.Design/methodology/approach We employ district-level unbalanced panel data from Pakistan from various rounds of Pakistan Social and Living Standards Measurement Surveys and Multiple Indicators Cluster Surveys compiled by the Data4Pakistan, Pakistan District Development Portal. We examine the impact of the percentage of the population in a given district with access to clean drinking water on the percentage of stunted, underweight and wasted children in the district. The analysis proceeds in two steps. In the first step, we explore the spatial distribution of improved drinking water coverage and child development outcomes across districts. In the second step, we study their relationship by employing standard panel estimation methods and controlling for district characteristics.Findings The spatial analysis reveals the large disparity among districts and provinces in terms of improved drinking water coverage and child nutrition. The estimation results indicate that there is a significant association between the accessibility of improved drinking water and child development outcomes. The effect is significant for child stunting and underweight but not for child wasting. The impact appears to be stronger in rural districts. These findings are robust to alternate empirical strategies.Originality/value This is the first such study to examine the provision of improved drinking water at the district level in relation to child developmental outcomes in a developing country context.Peer reviewThe peer review history for this article is available at: https://publons.com/publon/10.1108/IJSE-09-2023-0739